Analysis of Market Capitalization and Fundamental Factors on Firm Value - Irma Sari Permata; Fatima Tuzzahara Alkaf (DINASTI RESEARCH, 2020)
The purpose of this study is to analyze the effect of market capitalization and fundamental factors on the value of manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2018. The variables utilized in this study are market capitalization, variables of micro-company such as company size, free cash flow, dividend policy (DPR), and macro variables, namely interest rates to the value of the company (Tobin'Q). Therefore it can be to assess the development of good company conditions. The method of this research is explanatory research and samples were taken by purposive sampling from a population of manufacturing companies that satisfy the sample criteria. Furthermore, the analysis of this research conducted multiple linear regression analysis.